Utilization of Aspergillus niger fungus as an efficient use of inorganic phosphate (P) fertilizer in Edamame (Glycine max (L.) Merrill) - Abdullah Shoffahul Habib; Christa Dyah Utami (International Integrated Agricultural Journal (IIAJ), 2025)
Optimizing the use of inorganic P fertilizer through phosphate dissolution by the fungus Aspergillus niger, thus providing phosphate elements for edamame plants. This study aims to examine the growth and yield response of edamame plants (Glycine max (L.) Merril) to the application of phosphate solubilizing fungus (Aspergillus niger) in the efficiency of reducing the use of P fertilizer. This research was conducted in the field of Kebonsari Village, Sumbersari District, Jember Regency from July to November 2024. This study used a non-factorial Randomized Group Design (RAK) consisting of 5 levels, namely: 0 ml Aspergillus niger fungus/plant + 100% TSP, 10 ml Aspergillus niger fungus/plant + 75% TSP, 20 ml Aspergillus niger fungus/plant + 75% TSP, 30 ml Aspergillus niger fungus/plant + 75% TSP, 40 ml Aspergillus niger fungus/plant + 75% TSP. The results showed that the application of Aspergillus niger fungus was able to optimize the use of inorganic P fertilizer. The dose of Aspergillus niger fungus did not show a significant effect on the parameters of plant height, number of productive branches, number of pods per sample, weight of pods per sample, root length, and fresh weight of plants.